Effect of viaminate capsule combined with Xiaoyin particles on serum VEGF, TNF, NO, interleukins and T lymphocyte subsets in patients with psoriasis - Ping Zhao (Journal of Hainan Medical University, 2016)
Objective: To study the effect of viaminate capsule combined with Xiaoyin particles on serum VEGF, TNF, NO, interleukins and T lymphocyte subsets in patients with psoriasis. Methods: A total of 90 patients with psoriasis in our hospital from May 2014 to May 2016 were enrolled in this study. The subjects were divided into the control group (n=45) and the treatment group (n=46) randomly. The control group were treated with viaminate capsule, the treatment group were treated with viaminate capsule combined with Xiaoyin particles. The two groups were treated for 3 months. The serum VEGF, TNF-α, NO, IL-6, IL-8, IL-1β levels and peripheral blood CD4+ and CD8+ cells of the two groups before and after treatment were compared.Results: There were no significantly differences of the serum VEGF, TNF-α, NO, Interleukins (IL-6, IL-8, IL-1β) levels and peripheral blood CD4+ , CD8+ and CD4+ /CD8+ cells of the two groups before treatment (P>0.05). The serum VEGF, TNF-α, NO, Interleukins (IL-6, IL-8, IL-1β) levels of the two groups after treatment were significantly lower than before treatment (P<0.05), and that of treatment group were significantly lower than the control group (P<0.05). The peripheral blood CD4+ and CD4+ /CD8+ cells of the two groups after treatment were significantly higher than before treatment (P<0.05), CD8+ cells of the two groups after treatment were significantly lower than before treatment (P<0.05), the peripheral blood CD4+ and CD4+ /CD8+ cells of the treatment group after treatment were significantly higher than that of the control group (P<0.05), but there was no significantly differences in the peripheral blood CD8+ cells of the two groups after treatment (P>0.05). Conclusions: Viaminate capsule combined with Xiaoyin particles can significantly reduce the serum VEGF, TNF-α, NO, IL-6, IL-8 and IL-1β levels, improve the T lymphocyte subgroup levels of the patients with psoriasis, and it was worthy clinical application.